RISKS OF PEDAGOGICAL INNOVATIONS IN HIGHER EDUCATION - Natalia A. Lyz'; Alexander E. Lyz' (Moscow Polytechnic University, 2016)
In the light of social trends the requirements to the educational outcomes and accordingly to the educational process in higher education have been significantly modified.The purpose of this article is to analyze the models of educational process that meet the trends in higher education, to analyze the readiness of education subjects to implement them, to identify possible risks of important pedagogical innovations. The basic directions of innovation in higher education are systematized in the article. It is shown that the pedagogical innovations should provide constructive character of learning and activation of students' personal mechanisms of professional development. At the sam e ti meimplementation of new educational technologies is a necessary but not sufficient condition for the transition to a new quality of educational outcomes. The essence of the educational process related to the nature of the interaction between its subjects can be changed only through the development of students' personal resources and through formation of teachers' new professional-pedagogical position. Otherwise risks of falsification and imitation mayarise in modernized educational systems.